The Future of Rural Tourism in Bali, Indonesia: The Role of Social Media Platform - I Made Suniastha Amerta; Ida Bagus Udayana Putra; Ni Wayan Sitiari; Ilham Sentosa; Farah Hida Sharin (Centre of Excellence in Tourism Udayana University, 2025)
Digital transformation in Indonesia encourages the development of rural tourism as an instrument for local economic recovery. This study aims to test a Theory of Planned Behavior (TPB)-based model that integrates the role of Social Networking Sites (SNS) on the intention to participate in rural tourism and its impact on sustainability. The research method uses a quantitative survey with a convenience sampling approach. Data was collected through a Google Form which was distributed to 130 student respondents. Data analysis was carried out using SmartPLS to test structural models and relationships between variables. The results of the analysis showed that attitudes, subjective norms, and perceived behavioral control had a significant effect on the intention to participate in rural tourism. The use of social media has been shown to moderate the relationship between the SDG variables and the intention to participate. These findings confirm the validity of the proposed model. The implications of the research provide a theoretical contribution to the development of the SDG model in the context of digital tourism and practical for rural destination managers in designing social media-based marketing strategies. The limitations of research related to the use of convenience sampling require careful interpretation of the results regarding their external validity.